Animal-matière versus animal-enfant - Jean Nizet (Recherches Sociologiques et Anthropologiques)
There is broad consensus among sociologists and anthropologists studying human-animal relations that a fundamental divide exists between livestock animals, on the one hand, and companion animals, on the other. In the terminology of Stépanoff (2021:10), the former are treated as “material”, whereas the latter are cherished as “children”. This article acknowledges this divide and seeks to examine its origins. Adopting a socio-historical approach (Noiriel, 2006), it first aims to reconstruct the trajectories of these two categories of animals and identify the historical bifurcation – the moment at which they diverged. This socio-historical investigation is then subjected to theoretical analysis, undertaking both descriptive and explanatory work. On the descriptive level, the study aims to refine the distinction between these two animal populations, focusing primarily on two criteria: one concerning the similarities versus differences between humans and animals, and the other emphasizing proximity versus distance between the two. As for the explanation of this bifurcation and the subsequent trajectories, the study adopts the hypothesis that capitalism – and more specifically, its various “transformative forces” (Beaud, 2010), such as profit-seeking, scientific and technological advancements, and ideological shifts – played a central role in shaping these developments.